2016
DOI: 10.1016/j.jmbbm.2015.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behavior of biofunctional titanium oxide films produced by micro-arc oxidation: Synergism and mechanisms

Abstract: Dental implants, inserted into the oral cavity, are subjected to a synergistic interaction of wear and corrosion (tribocorrosion), which may lead to implant failures. The objective of this study was to investigate the tribocorrosion behavior of Ti oxide films produced by micro-arc oxidation (MAO) under oral environment simulation. MAO was conducted under different conditions as electrolyte composition: Ca/P (0.3M/0.02M or 0.1M/0.03M) incorporated with/without Ag (0.62g/L) or Si (0.04M); and treatment duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 55 publications
3
15
0
10
Order By: Relevance
“…This is also in good agreement with the significantly reduced wear loss in NT-Ca/P/Zn samples when compared to NT samples (Fig. 5), since a higher hardness is generally correlated with an improved wear resistance (Marques et al, 2016;Alves et al, 2013;Karthikeyan and Vijayaraghavan, 2016;Oliveira et al, 2015). Once NT-Ca/P/Zn films display improved adhesion properties to the substrate, consequently they display an improved ability to resist to mechanical wear.…”
Section: Mechanical Properties Of Tio 2 Nts: Significance and Impact supporting
confidence: 86%
See 1 more Smart Citation
“…This is also in good agreement with the significantly reduced wear loss in NT-Ca/P/Zn samples when compared to NT samples (Fig. 5), since a higher hardness is generally correlated with an improved wear resistance (Marques et al, 2016;Alves et al, 2013;Karthikeyan and Vijayaraghavan, 2016;Oliveira et al, 2015). Once NT-Ca/P/Zn films display improved adhesion properties to the substrate, consequently they display an improved ability to resist to mechanical wear.…”
Section: Mechanical Properties Of Tio 2 Nts: Significance and Impact supporting
confidence: 86%
“…Various studies have shown that TiO 2 nanoparticles are internalized by bone cells impairing their functions (Ribeiro et al, 2016) and activating inflammatory reactions which may induce to osteolysis, and ultimately to implant failure (Cobelli et al, 2011;Fisher, 2005, 2000). Therefore, the study of the degradation mechanisms of Ti and Ti-based materials by tribocorrosion mechanisms has been increasingly investigated over the past years (Sampaio et al, 2016;Toptan et al, 2016Toptan et al, , 2017Buciumeanu et al, 2017;Hacisalihoglu et al, 2015;Mathew et al, 2012;Souza et al, 2012Souza et al, , 2015Villanueva et al, 2017;Cruz et al, 2015;Runa et al, 2013;Geringer and Macdonald, 2014;Sivakumar et al, 2011;Marques et al, 2016). However, despite the growing attention on the development of new implant systems based on TiO 2 nanotubular platforms, the study of their degradation behavior by tribocorrosion processes is still very limited in literature.…”
Section: Introductionmentioning
confidence: 99%
“…As oppose to the as-etched samples, after sliding, the OCP values were stabilized at relatively lower values for all functionalized samples, as compared to the initial values, suggesting a permanent damage on the anodic oxide layer, as it had also been reported in the literature for the anodized dense surfaces (Alves et al, 2013;Fazel et al, 2015;De Viteri et al, 2016;da et al, 2016). Even though, the stabilization values after sliding were always much higher as compared to the ones recorded for the as-etched samples.…”
Section: Evolution Of Ocpsupporting
confidence: 62%
“…Marques et al [128] evaluated the tribocorrosion behavior of the oxide films containing P, Ca, Si, and Ag, developed in the previous work [118]. Coherently with the former results, the higher amount of Ca led to higher rutile crystalline phase formation on the coating, which was found to possess higher corrosion and tribocorrosion resistances.…”
Section: Enhancement Of Titanium Biomedical Implants Properties By Pementioning
confidence: 97%